The Effect of the CTL Model on Students’ Critical Thinking Skills in Static Fluids - Irfan Daniel; Erina Hertanti; Fuji Hernawati Kusumah (Jurnal Penelitian Pembelajaran Fisika, 2026)
The low level of students' critical thinking skills in physics subjects especially fluids static is a problem that includes understanding concepts and applying knowledge in real-world contexts. This study aims to examine the effect of the Contextual Teaching and Learning (CTL) model on students’ critical thinking skills in the topic of static fluids. A quasi-experimental method with a non-equivalent control group design was employed involving 66 eleventh-grade students at SMA Negeri 98 Jakarta, divided into an experimental group receiving CTL instruction and a control group taught using conventional methods. Critical thinking data were collected through a test based on Tiruneh’s indicators and analyzed using the Independent Sample T-Test and N-Gain calculation. The results indicate a significance value of 0.022 (< 0.05) and an N-Gain of 0.60 for the experimental group, higher than the control group’s 0.43. These findings demonstrate that CTL significantly enhances students’ critical thinking skills. The implications suggest that CTL is suitable for physics learning, especially for abstract topics such as static fluids, to strengthen cognitive skills and promote more meaningful learning.